Pathways for Ukraine’s post-war nature recovery: Focus on forest socio-ecological systems - Mariana Melnykovych; Maria Nijnik; Oleksandr Soshenskyi; Sergiy Zibtsev; Ganna Lobchenko; Simo Sarkki; Natalia Voloshyna; Ihor Soloviy; Pavlo Kravets; Yevhenii Khan; Roman Yaroshchuk; William S. Keeton; et al. (Ambio, 2026)
Natural ecosystems face significant pressure from climate change, biodiversity loss, and increasing socio-economic and political stressors—all of which are exacerbated by military conflict. This paper focuses on Ukraine and examines the root causes of disturbances in the country’s forest socio-ecological systems (SES), as well as the impacts of the ongoing war, to identify recovery pathways. Using a multi-method approach, we assess factors affecting Ukraine’s forest SES and identify three key recovery pathways: (1) an economic focus through forest use for low-carbon recovery, including timber for reconstruction and small-scale energy production; (2) a “close-to-nature and close-to-people” approach, leveraging digital tools and innovations for climate-resilient recovery; and (3) anticipatory governance and socio-ecological innovation. Relying on a single pathway risks long-term vulnerability. We highlight that integrating recovery pathways creates synergies. Coordinated actions within Ukraine and from international actors are essential to enable a recovery aligned with “build back better” principles. Our findings offer valuable insights for Ukraine and other conflict-affected regions. Graphical abstract

Improving propagation methods of Gnetum africanum and G. buchholzianum from cuttings for rapid multiplication, domestication and conservation - Oumar Doungous; Emile Minyaka; Samson D. Medza-Mve; Apollin F. Medueghue; Mercy A. Ngone; Claude Simo; Armand M. Nsimi (Agroforestry Systems, 2019)